Physician-reported treatment outcomes for ADHD among children and adolescents in Europe. (December 2013) - Setyawan, Juliana; Fridman, Moshe; Hodgkins, Paul; Quintero, Javier; Erder, M Haim; Katić, Božena; Harpin, Valerie
SUMMARY Aims: The aim of this study was to describe associations between physician-reported patient characteristics, treatment modalities and assessed outcomes in children diagnosed with ADHD in six countries.Methods: Clinical records of ADHD patients were retrospectively reviewed by treating physicians. Patients had optimal treatment success (OTS) if the physician assessed them as having complete symptom control and was highly satisfied with treatment.Results: Out of the 708 patients, 505 (71.3%) were treatment adherent. OTS was reported in 28.1% of patients (33.7% adherent and 14.3% nonadherent; p < 0.0001). Among adherent patients, there was no association between treatment type and OTS. Multivariate logistic regression models suggest that patients achieving OTS were more likely to have fewer comorbidities and lower reported impairment levels for ADHD-associated symptoms/behaviors.Conclusion: Overall, OTS was low. Among adherent patients, those with more comorbidities/greater ADHD impairment achieved lower OTS. There was no difference between treatment modalities, suggesting that opportunities exist to develop improved ADHD treatments.